IMPLIKASI STORE ATMOSPHERE, KUALITAS PRODUK, PERSEPSI HARGA, DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN DI EUPHORIA CAFÉ KARANGANYAR - Muhammad Akbar Wisnu Mumpuni; Andri Nurtantiono (ITB AAS INDONESIA Surakarta, 2022)
This study aims to determine the effect of store atmosphere, product quality, price perception, and lifestyle on purchasing decisions at Euphoria Café Karanganyar. The type of research used is quantitative research with survey methods conducted on visitors to Euphoria Café Karanganyar. The results of the analysis using multiple regression analysis are store atmosphere, product quality, lifestyle have a significant effect on purchasing decisions at Euphoria Karanganyar, while price perceptions have no significant effect on purchasing decisions at Euphoria Café Karanganyar. Suggestions in this study are referring to the store atmosphere variable at Euphoria Karanganyar, further improving the attractive decorations and seating layouts on the first and second floors which are not only able to accommodate a large number of visitors but also add comfort when they visit. Referring to lifestyle variables, hanging out activities for visitors can become one of the lifestyles that are carried out, Euphoria Café Karanganyar can add game facilities that are not yet available such as board games, jenga, uno cards and others to attract more visitors to come to the cafe. . Referring to the product quality variable, especially with regard to the menus served, the café can add new products from food and beverages. Referring to the price perception variable, Euphoria Karanganyar must review the prices at the cafe and restaurant which are set periodically while taking into account the level of competition. Keywords: Store Atmosphere, Product Quality, Price Perception, Lifestyle, and Purchase Decision